Family Nutrition: Methodological Bases For The Practice Of Nutrionists - Rower, Helena; Massola, Gisele (Seven Editora, 2023)
Taking the lyrics of the song Família by the Titãs band as inspiration, the importance of expanding the techniques used by professional nutritionists and the therapeutic relationship for a successful nutritional follow-up beyond its traditional approach are discussed. In this thematic essay, music sets the tone in the presentation of the theoretical framework, encompassing research on the practice of nutritionists with families and their dynamics. The objective is to incite the theme by problematizing the nutritionist’s work and training, since this practice requires constant reflection and ability to think in a systemic way when working in a new specialty, both in public and private care. To this end, the question of the scope of work and the proposition of a process-based nutrition, centered on the individual and his family, are exposed, aiming at the promotion of health by transcending the already known dietary aspects towards a more comprehensive path. The results have brought out approaches in which individuals pay attention to themselves, their needs, desires and will to learn, elaborate, use and re-signify eating and life habits, thus helping and supporting the best appropriate choices for their own well-being as well as their family’s. DOI: https://doi.org/10.56238/colleinternhealthscienv1-117